1985
DOI: 10.1016/0014-5793(85)81291-6
|View full text |Cite
|
Sign up to set email alerts
|

Optical difference spectrum of the electron acceptor Aoin photosystem I

Abstract: Photosystem I Primary acceptor Optical difference spectrum Chlorophyll a monomer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

1986
1986
1997
1997

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…This chlorophyll molecule is thought to have an absorption peak centred at 670 nm (Mansfield and Evans 1985) and would be clearly distinguishable from P700 in Fig. 2. The absence of such a signal in our data suggests a more complex action of A0 than simply a "metastable" electron acceptor.…”
Section: Discussionmentioning
confidence: 99%
“…This chlorophyll molecule is thought to have an absorption peak centred at 670 nm (Mansfield and Evans 1985) and would be clearly distinguishable from P700 in Fig. 2. The absence of such a signal in our data suggests a more complex action of A0 than simply a "metastable" electron acceptor.…”
Section: Discussionmentioning
confidence: 99%
“…Thus because the quadrilateral de®ned by the centroids of eC 2 , eC H 2 , eC 3 and eC H 3 is roughly coplanar with the C 2 (AB) axis (Figure 8(c)), each of eC 3 and eC H 3 is largely equidistant to both eC 1 and eC H 1 . On account of their position, approximately half-way between P700 and F X , and by analogy to the position of bacteriopheophytins in PbRC, at least one of them is assumed to be equivalent to the spectroscopically characterized primary acceptor, A 0 , proposed to be a Chla monomer (Mans®eld & Evans, 1985;Brettel, 1997).…”
Section: Primary Electron Acceptormentioning
confidence: 99%
“…However, the results of flash absorption measurements on the recombination of P~00A? Recently, using photo-accumulation techniques, Mansfield and Evans (1985) poised PSI particles in the states P700m0A~ -and P700m0-A~-and determined the absorption difference spectra of A~/Ai-and A0/A0-• It was found that there were no absorption changes in the range of 350-750 nm due to the reduction of A~. Moreover, using Q-band EPR (35 GHz microwave frequency) evidence was found for substantial g-anisotropy in the EPR spectrum of A1, which conflicts with the idea that A~ is a chlorophyll-like molecule (Thurnauer and Gast 1985).…”
Section: Introductionmentioning
confidence: 99%